Otimização de vigas seção T de concreto armado submetidas a flexão simples - Romano, Matheus Drago (2021)
This work aims to develop a restricted non-linear programming problem that determines the optimized cross section of reinforced concrete T beams, as well as its computational implementation, establishing the lowest construction cost, ensuring the static balance of the cross section and meeting to constructive restrictions and those established by ABNT NBR 6118:2014. For the computational implementation of the mathematical minimization algorithm applied to the model, the MATLAB software and the fmincon function present in its optimization auxiliary library were used. In this function, the Interior Points Method was used as an iterative method to determine the optimal solution of the restricted problem. To perform analyzes and establish comparisons, two different models were developed, and for each of them, it aimed, individually, to meet the restrictions of the ABNT NBR 6118:2014 standard, and meet the restrictions imposed by ABNT NBR 6118:2003. The results are significant in the context of optimizing the cost of the modeled problem and demonstrate the individual contribution of material costs in the composition of the final cost of T beams.